THE INFLUENCE OF ADVERTISING STARS, BRAND IMAGE, AND BRAND AWARENESS ON THE INTENTION TO BUY HONDA VARIO MOTORCYCLES IN PASURUAN - Bastian, Antoni; Sugito, Sugito; Hati Wau, Kerinus; Nastiti, Wahyuningsih; Sutismawati Sirait, Lincaria (Sinergi : Jurnal Ilmiah Ilmu Manajemen, 2019)
This study examines the Influence of Advertising Stars, Brand Image, and Brand Awareness Against Intention to Buy Honda Vario Motor in Pasuruan. The purpose of this research is to know the direct and indirect correlation between the influence of advertisement star to brand image and brand awareness. The results show that the indirect effect on brand awareness is mediated by brand image. Honda Vario brand image is so strong that it can increase the value contained in the product. Companies must use variables and do different strategies so that their products become more desirable in the market.